Inhibition of Streptococcus mutans biofilm formation and virulence by natural extract Stevioside - Ma, Rong; Wang, Peiling; Zhang, Yuanyuan; Wang, Yimin; Chu, Jinpu (Frontiers in Microbiology, 2025)
ObjectiveThis study aimed to investigate the effect of the natural extract of Stevioside on biofilm formation and cariogenic virulence factors of Streptococcus mutans (S. mutans), and to explore its mechanism of action preliminarily, with the goal of identifying a safer and more effective non-cariogenic sweetener.MethodsThe inhibitory effect of Stevioside on the growth of S. mutans biofilm was detected by crystal violet staining. The acid production capacity of S. mutans biofilms was evaluated by measuring the pH values and lactic acid contents. The bacterial viability within the biofilms was determined using the plate counting method. Scanning electron microscopy (SEM) and laser confocal microscopy (CLSM) were used to observe the biofilm structure, and the fluorescence intensity of live and dead bacteria and biofilm thickness were further analyzed. The anthrone sulfuric acid method quantified the production of Soluble Extracellular Polysaccharide (SEPS) and Insoluble Extracellular Polysaccharide (IEPS) in biofilm. Furthermore, real-time fluorescence quantitative PCR (RT-qPCR) was used to detect the expression of genes related to biofilm growth, acid production, acid tolerance, exopolysaccharide synthesis, two-component signal and quorum sensing.ResultsStevioside significantly inhibited the formation of S. mutans biofilm, and reduced acid production, bacterial activity and EPS production. SEM and CLSM confirmed the reduction of the dense three-dimensional structure of biofilm. In addition, compared with sucrose, the expression of related genes was down-regulated in Stevioside.ConclusionStevioside inhibits S. mutans virulence factors and biofilms and is a promising natural sucrose substitute for preventing dental caries.